Vicki Belo ang batang nagpalaganap ng ganda The girl who spread beauty - Evasco, Eugene Y. (Chikiting books, 2013)
"This book narrates the story of Dr. Vicki Belo's life--how a shy child transformed and became a successful cosmetic surgeon in the Philippines. The story highlights Vicki's extraordinary diligence to improve herself, her knowledge, and abilities, to become successful with her business ventures."